Parâmetros acústicos, perceptivo-auditivos, aerodinâmicos, eletroglotográficos, laríngeos e de autopercepção da voz: análise do efeito da nebulização - Bárbara Oliveira Souza (2019)
Introduction: Hydration for voice professionals is one of the most important vocal hygiene habits in maintaining vocal health. Behavioral dysphonia manifests when a change in the vocal fold vibration pattern, which may be caused by improper functional adjustments; by lesions in the vocal fold mucosa; or by the association of both factors. Studies show that there are two types of hydration procedures: the internal or systemic, which refers to the intake of water or electrolytes, and the external, which refers to the inhalation of water or saline. Purpose: To verify the effect of nebulization on acoustic, perceptual, aerodynamic, electroglottographic, laryngeal and voice self-perception parameters of individuals with and without dysphonia. Methodology: This is a clinical study, intrasubjects comparative. Were selected 64 adults young, dysphonic and with normal voice, 30 female and 34 male. All subjects were research underwent vocal, laryngeal and self-perceived voice evaluation, and then remained at vocal rest for 10 minutes and analyzes were performed again. After this first stage, all participants underwent nebulization for 10 minutes and the procedures described above were once again performed. The analysis of the variables was firstly descriptive through absolute and relative frequency distribution of categorical variables and numerical synthesis measures of quantitative variables. Intra-rater agreement on auditory-perceptual assessment was assessed using AC1 statistics. From the analysis of the distribution of the quantitative variables through the Kolmogorov-Smirnov test, the statistical test to be used to compare the pre and post nebulization groups (Paired Student's T test and Wilcoxon test) was defined. Results and Discussion: The results and discussion will be presented in the form of a scientific article to be submitted in the Journal of Voice, entitled "The saline nebulization improves voice, mucocondulatory movement of vocal folds and vocal self-perception of men and women."